Experimental Study and Mathematical Modeling of Hydrogen Sulfide Removal from Biogas - M. Zarei; M. R. Bayati; M. A. Ebrahimi-Nik; B. Hejazi; A. Rohani (Journal of Agricultural Machinery, 2023)
IntroductionAnaerobic bacteria break down organic materials like animal manure, household trash, plant wastes, and sewage sludge during the anaerobic digestion process of biological materials and produce biogas. One of the main issues in using biogas is hydrogen sulfide (H2S), which can corrode pipelines and engines in concentrations between 50 and 10,000 ppm. One method for removing H2S from biogas with minimal investment and operation costs is biofiltration. Whether organic or inorganic, the biofilter's bed filling materials must adhere to certain standards including high contact surface area, high permeability, and high absorption. In this study, biochar and compost were used as bed particles in the biofilter to study the removal of H2S from the biogas flow in the lab. Afterward, kinetic modeling was used to describe the removal process numerically.Material and MethodsTo remove H2S from the biogas, a lab-sized biofilter was constructed. Biochar and compost were employed separately as the material for the biofilter bed. Because of its high absorption capacity and porosity, biochar is a good choice for substrate and packed beds in biofilters. The biochar pieces used were broken into 10 mm long cylindrical pieces with a diameter of 5 mm. Compost was used as substrate particles because it contains nutrients for microorganisms. Compost granules with an average length of 7.5 mm and 3 mm in diameter were used in this study. For the biofilter reactor, each of these substrates was put inside a cylinder with a diameter of 6 cm and a height of 60 cm. The biofilter's bottom is where the biogas enters, and its top is where it exits. During the experiment, biogas flowed at a rate of 72 liters per hour. Mathematical modeling was used to conduct kinetic studies of the process to better comprehend and generalize the results. This method involves feeding the biofilter column with biogas that contains H2S while the biofilm is present on the surface of the biofilter bed particles. The bacteria in the biofilm change the gaseous H2S into the harmless substance sulfur and store it in their cells. The assumptions that form the foundation of the mathematical models are: the H2S concentration is uniform throughout the gas flow, the gas flow is constant, and the column's temperature is constant at a specific height.Results and DiscussionIn the beginning, biochar was used as a substrate in the biofilter to test its effectiveness, and the results obtained for removing H2S from the biogas were acceptable. H2S concentration in biogas was significantly reduced using biochar beds. It dropped from 300 ppm and 200 ppm to 50 ppm where the greatest H2S concentration reduction was achieved. The level of Methane in the biogas was not significantly impacted by the biofilter. This is regarded as a significant outcome when taking into account the goal which is producing biogas with a high concentration of methane. The H2S elimination effectiveness was 94% with the biochar bed and biogas input with 185 ppm H2S concentration. The removal efficiency reached 76% with the compost bed and input concentration of 70 ppm. Using mathematical models, the simulation was carried out by modifying the model's parameters until the predicted results closely matched the experimental data. It may be concluded that the suggested mathematical model is sufficient for the quantitative description of H2S removal from biogas utilizing biofilm in light of how closely the calculation results matched the experimental data. The only model parameter that was changed to make the model results almost identical to the experimental data was the value of the maximum specific growth rate (μmax) which has the greatest influence on the model results. The value of μmax for the biochar bed was calculated as 0.0000650 s-1 and for the compost bed at 70 ppm and 35 ppm concentrations as 0.0000071 s-1 and 0.0000035 s-1, respectively.ConclusionThe primary objective of this study is to examine the removal of H2S from biogas using readily available and natural substrates. According to the findings, at a height of 60 cm, H2S concentration in biochar and compost beds decreased from 185 ppm to 11 ppm (removal efficiency: 94%) and from 70 ppm to 17 ppm (removal efficiency: 76%), respectively. The mathematical models that were created can quantify the H2S elimination process, and the μmax values in biochar and compost were calculated as 0.0000650 s-1 and 0.0000052 s-1, respectively.AcknowledgmentThe authors would also like to thank UNESCO for providing some of the instruments used in this study under grant number No. 18-419 RG, funded by the World Academy of Sciences (TWAS).